Repeated Low-Intensity Shock Wave Simulation Experiment for Fracture Development and Propagation of Coal. (26th May 2019) - Xie, Taofeng; Zhou, Xiaoting; Wang, Qingya; Cao, Shuai; Cao, Huiming; Huang, Wengang
Abstract : For low-permeability coal seam, the gas extraction rate is relatively low. The repeated low-intensity shock wave can improve the permeability of coal and raise the rate of coal seam gas drainage. A simulation test platform was set up to carry out repeated low-intensity shock wave simulation experiment. Under the effect of repeated low-intensity shock wave, the development process of the macrofracture, pore evolution, and the law of microcrack propagation was analyzed to study the law of coal fracture propagation. Research shows that the expansion of the pore of the coal is made by the development of large, medium, and micropores by the repeated low-strength shock wave. The main contribution of the total pore volume increase comes from the micropore growth. The microcrack of the coal mainly begins to sprout and develops from the telocollinite where the fracture is more developed. With the increase of impact times, the microcracks extend to other components. Under the impact of different times, the fractal dimension of the coal sample increases with the increase in the number and length of cracks.